The absence of Baroque ornamentation in performing baroque music on the classical guitar among UiTM music students / Muhammad Adil Putera Badrul Hisham - Badrul Hisham, Muhammad Adil Putera (2013)
Faculty of Music UiTM Shah Alam offered Bachelor of Music Performance course in order to find a performer for next generation. In order to become a true performer, student need to fulfill the requirements of being a performer such as technical difficulties, performing skills, and interpretation of music. Classical guitar is one of the instruments which have been offered by the Faculty of Music for the principle studies as the main instrument for students. Classical guitar nowadays has been attracted by some compositions. Transcribed piece, new compositions has given the classical guitar an opportunity to become one of well-known instrument in music world nowadays and also give classical guitar to perform in concert hall. Classical guitar uses nylon strings, plucked with the fingers, played in a seated position and is used to playa diversity of musical styles including classical music. There are other types of guitars such as electric guitar and acoustic guitar which are being played in other styles of music. Each type of guitar plays an important role in producing the music. For instance, rock music genre uses a distortion sound and the characteristic of clean sound added a different dimension to the jazz ensemble (Stimpson M. 1988).